Money and masohi; An anthropological review of copra commodity management - Rudyansjah, Tony; Tihurua, Ode Zulkarnain Sahji (UI Scholars Hub, 2019)
In discussions on exchange, as well as an object in gift exchange money is often seen as a medium of exchange and a universal equivalent in the circulation of commodities. However, in the case of the management of the copra commodity which we researched on the island of Seram, money had become a factor in shaping a dynamic of gift continuity and transformation in the realm of the copra economy (in this context of the customary practice masohi). It transpires that money has promoted both the observance and erosion of masohi custom. Masohi is a tradition of community work in the island of Seram. It is based on non-capitalist social relations and the principle of reciprocal exchange. This article seeks to describe how money, originally a capitalist medium, has simultaneously served to preserve and transform masohi, which, in its essence, is a non-capitalist institution.